2022
DOI: 10.3390/antiox11112093
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin, a Promising Dietary Supplement for Preventing the Development of Calcific Aortic Valve Disease

Abstract: Background: No effective therapeutic agents for calcific aortic valve disease (CAVD) are available currently. Dietary therapy has been proposed as a novel treatment strategy for various diseases. As a flavanone, hesperetin is widely abundant in citrus fruits and has been proven to play a protective role against multiple diseases. However, the role of hesperetin in CAVD remains unclear. Methods: Human aortic valve interstitial cells (VICs) were isolated from aortic valve leaflets. A mouse model of aortic valve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…hampering the release of pro-inflammatory cytokines and ROS production, mitigati dysfunctional mitochondria, via the upregulation of Nrf2 [200].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hampering the release of pro-inflammatory cytokines and ROS production, mitigati dysfunctional mitochondria, via the upregulation of Nrf2 [200].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that HSP was able to target SIRT7, exerting a protective effect against calcific aortic valve disease both in vitro and in vivo. This effect was due to HSP's capability to directly bind SIRT7, hampering the release of pro-inflammatory cytokines and ROS production, mitigating dysfunctional mitochondria, via the upregulation of Nrf2 [200].…”
Section: Sirt7mentioning
confidence: 99%
See 1 more Smart Citation
“…Hesperetin is a flavonoid mainly found in citrus fruits and has been known to possess antioxidant and anti-inflammatory activities [ 13 , 14 ]. Accumulating evidence suggests that this compound exerts beneficial effects on a variety of inflammatory diseases, including obstructive kidney disease and diabetic nephropathy [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In this study, hesperetin alleviated structural and functional renal injury in LPS-injected mice, as evidenced by the amelioration of histological tubular damage, attenuation of the brush border loss, downregulation of the tubular injury marker, and a reduction in serum creatinine and BUN levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperetin is a natural flavonoid that has antioxidant and anti-inflammatory properties [ 13 , 14 ]. Administration of hesperetin can ameliorate myocardial ischemia [ 15 ], calcific aortic valve disease [ 16 ], fatty liver disease [ 17 ], osteoarthritis [ 18 ], colitis [ 19 ], acute lung injury [ 20 ], and Alzheimer’s disease [ 21 ] in rodents. In addition, hesperetin can alleviate unilateral ureteral obstruction-induced renal injury and fibrosis through inhibiting epithelial–mesenchymal transition in mice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%